2021
DOI: 10.1021/acs.jpcb.1c02739
|View full text |Cite
|
Sign up to set email alerts
|

Fast ATP-Dependent Subunit Rotation in Reconstituted FoF1-ATP Synthase Trapped in Solution

Abstract: F o F 1 -ATP synthases are ubiquitous membrane-bound, rotary motor enzymes that can catalyze ATP synthesis and hydrolysis. Their enzyme kinetics are controlled by internal subunit rotation, by substrate and product concentrations, and by mechanical inhibitory mechanisms but also by the electrochemical potential of protons across the membrane. Single-molecule Forster resonance energy transfer (smFRET) has been used to detect subunit rotation within F o F 1 -ATP synthases embedded in freely diffusing liposomes. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 76 publications
0
24
0
Order By: Relevance
“…In contrast, the authors of a comparable study have argued that the high FRET level is a representative of two states that are indistinguishable due to the geometry of the fluorescent labels during rotation. 46 In this case, even if the two states cannot be distinguished by FRET levels, one would expect the enzyme to rest in the high level twice as long as in the low level. Instead, the authors observed two subpopulations with comparable occurrence and duration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the authors of a comparable study have argued that the high FRET level is a representative of two states that are indistinguishable due to the geometry of the fluorescent labels during rotation. 46 In this case, even if the two states cannot be distinguished by FRET levels, one would expect the enzyme to rest in the high level twice as long as in the low level. Instead, the authors observed two subpopulations with comparable occurrence and duration.…”
Section: Resultsmentioning
confidence: 99%
“…The simple assignment of FRET levels to molecular states based on structural data and expected fluoropore distances can lead to inconsistancies within the dataset. 46 Detection techniques with immobilised samples and attached labels such as actin filaments, 44,47–50 gold nanorods 51,52 or beads 12,40 seem to have an advantage over single fluorophore detection in resolving rotational steps but risk obstruction by nearby surface interactions that can result in artificially increased dwell times. 37,40,53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our implementation of a fast FPGA-based ABEL trap was described earlier 6, 35 - 38, 44, 45 and was slightly modified here. Briefly, a linearly polarized continuous-wave laser emitting at 491 nm (Calypso, 50 mW, Cobolt) was attenuated to 40 μW.…”
Section: Methodsmentioning
confidence: 99%
“…The ABEL trap for quantitative single nanoparticle spectroscopy in solution was invented by A. E. Cohen and W. E. Moerner [31][32][33][34] . Here, we analyzed the brightness of the NTSR1-SMALPs in our confocal ABEL trap [35][36][37][38] . We found different fluorescence intensity levels in SMALPs derived from HEK293T cells expressing NTSR1-mNeonGreen either before or after stimulation with its ligand neurotensin.…”
Section: Introductionmentioning
confidence: 99%